2006
DOI: 10.1007/s10479-006-0042-7
|View full text |Cite
|
Sign up to set email alerts
|

Preference, Production and Performance in Data Envelopment Analysis

Abstract: In this paper, we re-examine Data Envelopment Analysis models from perspectives of preference order, production set and performance measure. we investigate the relationship between Data Envelopment Analysis (DEA) and Multiple Criteria Decision Making Theory.There are three key building blocks in a DEA model: preference order, production possibility set and performance measure. It is shown in this work that many known DEA models and new ones, can be derived via this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 23 publications
0
17
0
2
Order By: Relevance
“…In the standard DEA models like CCR and BCC, the classic Pareto preference is assumed, as in this work. However, we emphasize there are many real applications where different preferences are indeed useful, see Liu et al (2006) and Zhang et al (2009) for some examples. Let X = (x 1 , .…”
Section: Disposability Assumptions In Deamentioning
confidence: 99%
See 3 more Smart Citations
“…In the standard DEA models like CCR and BCC, the classic Pareto preference is assumed, as in this work. However, we emphasize there are many real applications where different preferences are indeed useful, see Liu et al (2006) and Zhang et al (2009) for some examples. Let X = (x 1 , .…”
Section: Disposability Assumptions In Deamentioning
confidence: 99%
“…Our main idea is to examine them within the general framework proposed in Liu et al (2006), where some essential building blocks of a DEA model were identified and illustrated. The principal objective of this paper is to discuss the free disposability assumptions and to describe a number of different performance measures or metric functions with attractive properties in the presence of undesirable inputs and outputs and negative data.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Similar models were studied in (Zhu 1996) to study economical development for cities in China. For more explanations of these models, see (Liu, Wu and Sharp, 2004). In the above DEA models, it is impossible to rank the efficient DMUs as their efficiency scores are the unit.…”
Section: Aggregated Efficiency Analysismentioning
confidence: 99%